Characterization and functional analyses of the human HTR1A gene: 5’ regulatory region modulates gene expression in vitro - Xue Wu; Feng-ling Xu; Mei Ding; Jing-jing Zhang; Jun Yao; Bao-jie Wang (BMC Genetics, 2018)
Abstract Background The serotonin neurotransmitter (5-HT) and its receptors have important roles in neuropsychiatric disorders such as schizophrenia. The aim of this study was to investigate the functional sequences of the 5′ regulation region of the human HTR1A gene to explore the effects on the expression of the 5-HT1A receptor. Methods Fourteen recombinant pGL3-basic vectors containing deletion fragments of the HTR1A gene regulatory region were transfected with HEK-293 and SK-N-SH cells. The relative chemiluminescence intensities of different length fragments were analyzed. The JASPAR software was used for the prediction of transcription factors. Results In the HEK-293 cells, the relative chemiluminescence intensity of the − 1649 bp to − 1550 bp (ATG + 1) fragment was significantly different. Two inhibitory activity regions were found in the − 1409 bp to − 1381 bp and − 1196 bp to − 1124 bp fragments, which might be bound to the GATA or SOX10 transcription factors as predicted by the JASPAR software. In addition, the fragments located from − 1124 bp to − 1064 bp and from − 908 bp to − 722 bp up-regulated protein expression. Only the sequence from − 1550 bp to − 1409 bp demonstrated a difference in luciferase expression in the both cell lines. According to the results of the 5’-UTR truncated vectors, there was a repression region at the distal end of the 5’-UTR, an enhancer region might be present at the proximal end of the transcription start site. Conclusions Although the functional sequences of the HTR1A gene regulatory region were confirmed, the regulatory factors and functional components require further investigation.